2012
DOI: 10.1002/app.38770
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical sensing of glucose using polyaniline nanofiber dendrites‐amperometric and impedimetric analysis

Abstract: A novel electrochemical synthesis of polyaniline (PANI) nanofiber dendrites on platinum electrodes using p‐toluenesulfonic acid for sensing of glucose is reported. The characterization of PANI is carried out using scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, and ultraviolet (UV)–visible spectral studies. The electrochemical behavior of the PANI‐coated electrode is investigated with the help of cyclic voltammetry, chronoamperometry, and impedance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…The PANI–MSF hybrid structure was further characterised by UV–visible absorption spectroscopic measurements. As reported previously, PANI thin films usually display three signature absorption bands centred at 342, 424 and 865 nm 22. The band at 342 nm arises from the π–π* transition, whereas those at 424 and 865 nm are due to the protonation of PANI backbone and formation of polarons, respectively 14a.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…The PANI–MSF hybrid structure was further characterised by UV–visible absorption spectroscopic measurements. As reported previously, PANI thin films usually display three signature absorption bands centred at 342, 424 and 865 nm 22. The band at 342 nm arises from the π–π* transition, whereas those at 424 and 865 nm are due to the protonation of PANI backbone and formation of polarons, respectively 14a.…”
Section: Methodssupporting
confidence: 53%
“…As reported previously, PANI thin films usually display three signature absorption bands centred at 342, 424 and 865 nm. [22] The band at 342 nm arises from the p-p* transition, whereas those at 424 and 865 nm are due to the protonation of PANI backbone and formation of polarons, respectively. [14a] In contrast, the PANI-MSF structure displays a rather different absorption spectrum ( Figure 5).…”
mentioning
confidence: 99%
“…It may be inferred that GOx immobilized electrodes does not have interference from the fact that its operation condition is negative potential. The potential used in this study is lower compared to previously reported potentials for sensing in mediated and non-mediated biosensors [44,45]. Since the present study contemplated devising a low cost electrode on an inexpensive substrate PC, only one-time usage was envisaged.…”
Section: Calibration Curve and Michaelis Menton Contant (Km)mentioning
confidence: 90%
“…To evaluate the biological activity of the enzyme, the apparent Michaelis-Menten constant (Km) for the calibration graph was obtained through the Lineweaver-Burke plot (Figure 6(c)) [44] = + 1…”
Section: Calibration Curve and Michaelis Menton Contant (Km)mentioning
confidence: 99%
“…12,13 This univariate approach disregards the possibility that there is more than one element of the equivalent electrical circuit presenting analyte concentrationdependent values, which is not unusual as can easily be seen in the literature. [14][15][16][17] Using more than one electrical component for predicting analyte concentration could bring advantages inherent to the multivariate calibration approach such as (i) possibility of providing extra (and often complementary) information to the calibration model for each element added, once different elements may be influenced differently by experimental noise or interferents; (ii) possibility of simultaneous analysis of multiple analytes; and (iii) possibility of detecting the presence of interferents (first-order advantage). 18 The use of multivariate calibration applied to EIS data for the development of analytical methods is scarce and is mainly based on latent structures methods such as partial least squares (PLS) and principal component regression (PCR) on EIS full spectrum represented as real or complex numbers.…”
mentioning
confidence: 99%